Cyclohexyl-Substituted Anthracene Derivatives for High Thermal Stability Organic Semiconductors - Dong, Yicai; Guo, Yuan; Zhang, Hantang; Shi, Yanjun; Zhang, Jing; Li, Haiyang; Liu, Jie; Lu, Xiuqiang; Yi, Yuanping; Li, Tao; Hu, Wenping; Jiang, Lang (Frontiers in Chemistry, 2019)
A novel p-type organic semiconductor with high thermal stability is developed by simply incorporating cyclohexyl substituted aryl groups into the 2,6-position of anthracene, namely 2,6-di(4-cyclohexylphenyl)anthracene (DcHPA), and a similar compound with linear alkyl chain, 2,6-di(4-n-hexylphenyl)anthracene (DnHPA), is also studied for comparison. DcHPA shows sublimation temperature around 360 oC, and thin film field-effect transistors of DcHPA could maintain half of the original mobility value when heated up to 150 oC. Corresponding DnHPA has sublimation temperature of 310 oC and the performance of its thin film devices decreases by about 50 % when heated to 80 oC. The impressing thermal stability of the cyclohexyl substitution compounds might provide guidelines for developing organic electronic materials with high thermal stability.